Aplikasi Pembayaran Administrasi Siswa Pada SMK Al Falah Songgom Brebes dengan Visual Basic - M. Al' Amin; M Mukholik (Jurnal Teknik Informatika dan Sistem Informasi, 2015)
Advancement of information systems and rapid technological support the advancement of an institution or agency. Applications of payment Administration vocational students Al Falah Songgom Brebes with Visual Basic is expected to provide benefits for the finance department to manage the administration of the student, so that the work can be completed quickly and to minimize mistakes that often occur in data processing and saves storage space. This study aims to build an administration payment student information system that is focused on the administration of student data processing payments. Applications of payment Administration vocational students Al Falah Songgom Brebes with Visual Basic was built by using Software Development Life Cycle (SDLC) that is by using the waterfall model. Administration payment student information system is built by using Visual Basic 6.0, MySQL for its database design, as well as Active Dynamic Data Report. Administration payment student information system includes the design of the system login screen, main menu form, the form data input majors, student data input form, form registration, form registration details, form of payment details, form of payment types, forms and database backup reporting form includes reports monthly and daily. From the test results information system has been able to help the finance department in managing financial administration students at SMK Al Falah Songgom Brebes and can be further developed into a better system again.Â Keywords: Applications of payment Administration, SDLC, Waterfall.Visual Basic 6.0, MySQL, Active Report